Let X be an exponential random variable with parameter 2. Find the CDF of X . Express your answer in terms of x using standard notation. Use 'e' for the base of the natural logarithm (e.g., enter e^(-3*x) for e−3x ). a) For x≤0 , FX(x)= unanswered b) For x>0 , FX(x)=

Respuesta :

Answer:

[tex]F(x,\lambda) = 1-e^{2x}[/tex]     for      [tex]x\geq0[/tex]

and   [tex]F(x,\lambda) = 0[/tex]    for   [tex]x <0[/tex]

Step-by-step explanation:

Remember that the CDF of an exponental random variable is given by

[tex]F(x,\lambda) = \left \{ {{1-e^{\lambda x} \ \ \ \ \ x\geq 0} \atop {0} \ \ \ \ \ \ \ \ \ \ \ x<0} \right.[/tex]

where   [tex]\lambda[/tex]   is the parameter.  In this case    [tex]\lambda = 2[/tex]  so, for this case

[tex]F(x,\lambda) = \left \{ {{1-e^{2x} \ \ \ \ \ x\geq 0} \atop {0} \ \ \ \ \ \ \ \ \ \ \ x<0} \right.[/tex]

Part(a) For [tex]x\leq 0,F_{x}\left ( x \right )=0[/tex]

Part(b) For [tex]x > 0,F_{x}\left ( x \right )=1-e^{-2x}[/tex]

Probability density function:

The probability density function (PDF) is used to define the random variable’s probability coming within a distinct range of values, as opposed to taking on anyone's value.

Part(a):

Given that,

[tex]x\sim Exp\left ( \lambda =2 \right )[/tex]

[tex]\therefore[/tex]The PDF of [tex]x[/tex] is

[tex]\Rightarrow f_{x}\left ( x \right )=\left\{\begin{matrix}\lambda e^{-\lambda x}=2.e^{-2x} \ ;for,x > 0 & \\ 0 \ ;otherwise & \end{matrix}\right.[/tex]

Define, [tex]F_{x}\left ( x \right )=p\left ( x\leq x \right )=cdf \ of \ x[/tex]

[tex]\Rightarrow[/tex]So, when [tex]x\leq 0;[/tex]we have,

[tex]F_{x}\left ( x \right )=p\left ( x\leq x \right )=0[/tex]

Part(b):

when [tex]x > 0;[/tex] we have,

[tex]x\leq 0,F_{x}\left ( x \right )=0 \\ x > 0,F_{x}\left ( x \right )=1-e^{-2x}x\sim Exp\left ( \lambda =2 \right ) \\ \Rightarrow f_{x}\left ( x \right )=\left\{\begin{matrix}\lambda e^{-\lambda x}=2.e^{-2x} \ ;for,x > 0 & \\ 0 \ ;otherwise & \end{matrix}\right. \\ F_{x}\left ( x \right )=p\left ( x\leq x \right )=cdf \ of \ x \\ F_{x}\left ( x \right )=p\left ( x\leq x \right )=0 \\ \x > 0;[/tex]

[tex]F_{x}\left ( x \right )=p\left ( x\leq x \right ) \\ =\int_{0}^{x}d_{x}\left ( t \right )dt \\ =\int_{0}^{x}2e^{-2t}dt\\=(1-e^{-2x})[/tex]

Learn more about the topic Probability density function:

https://brainly.com/question/10804981

ACCESS MORE